Modelación de un kart eléctrico utilizando openmodelica (2020)
The present work takes part of the BTA Racing group of the Universidad de los Andes, which built an electric kart. This project is focused on the development of a digital twin of that kart. The principal motivation of this is to make a computational model of the kart, because throughout it can be done several iterations under different frontier conditions, in this case diverse maneuvers (step steering, skidpad and acceleration), to evaluate the performance of it and lastly make changes to the physical model if it is pertinent. To achieve that, first it is introduced the vehicular dynamics (lateral and longitudinal) and described the different parts of the electric vehicle. It is worth to highlight that this work is the focused on doing the first iteration on the program OpenModelica with three different libraries: Modelica.Mechanics, Modelica.Blocks y wbEHPTlib. Next, a detailed description of the different blocks used is made with the due parameters. Lastly, the obtained results will be shown and it will be proposed some future work on the following iterations.